The Effect of Wordwall.net in the Teaching of Vocabulary at SMP Negeri 7 Tualang - Susilawati, Yollanda; Novitri, Novitri; Syarfi, M (Indonesian Journal of Education and Development Research, 2025)
This research aimed to determine the effect of using Wordwall.net in the teaching of vocabulary to seventh-grade students at SMP Negeri 7 Tualang. This study was motivated by the vocabulary gap experienced by students who switched from elementary schools implementing the 2013 Curriculum, where English is an elective subject, and in junior high schools implementing the Merdeka Curriculum, where English is a core subject. The research used a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 29 students selected through purposive sampling. Data were collected through vocabulary tests administered before and after treatment using Wordwall.net. The data analysis technique used is descriptive analysis. The data acquired in the Sig. column (2-tailed) is 0.000 (0.000 0.05). Besides, the value of t-count is higher than t-table (t-count t-table), which is 26.224 (26.224 2.048). It means that Ho is rejected and Ha is accepted. So, it can be concluded that the use of Wordwall.net has a significant effect on students' vocabulary mastery of seventh-grade students of SMP Negeri 7 Tualang. It is suggested that teachers incorporate Wordwall.net as a supporting medium to enhance vocabulary learning in an interactive and enjoyable way.